An integrated marketing communications campaign for BDO Debit Card with MasterCard - Carino, Cindy (Animo Repository, 2016)
Filipino consumers make payment transactions every day it has been part of their lifestyle. Firms and employers pay wages to their employees, then employees pay their purchases and buy things they need and want. This payment system is a never ending cycle, a major component of the countrys infrastructure system that no country can afford to take for granted. Therefore, it is ideal that advances in information technology and changes in laws and regulations must serve as the tools to achieve efficiency in the fast movement of funds among market participants for the progress of the economy. The technological advancement in the payment system introduced the use of electronic payment media that includes ATM debit cards which is a card-based payment instrument that allows consumers to have access to their bank deposits and use it to make cash withdrawals, payments at the point of sale (POS), pay bills and even online purchases. This integrated marketing campaign for BDO debit card with MasterCard discusses the fast growing usage of such payment card increase on its value and number of transactions, showing the promising growth of cashless transactions in the country. A survey was conducted by the researcher to verify the said claim and identify why consumers are encouraged to use it. Data gathered shows that the convenience experienced by the consumers using debit card is their main motivator. The target market who are Filipino Millennials age ranges from 23 to 34 years old, saw the benefits of using debit card in their payment transactions such as cash withdrawals, in-store purchases, bills payment and online purchases. These consumers aim for faster yet safer payment methods for their daily purchases. When both are achieved, it resonates convenience in all aspects. Based on the comprehensive data acquired and collated, the researcher created a creative plan that shows the convenience debit card provides to Filipino Millennials situated in key cities of the country. Understanding the personality and the buying behavior of the consumer leads to the researchers big idea paying can be this convenient. Ms Universe 2015, Pia Wurtzbach was chosen to be the face of the banks new debit card campaign paying can be this convenient. The newest addition to BDO Unibanks growing roster of endorsers, joining famous celebrities such as Piolo Pascual, Xian Lim, Richard Yap Ser Chief and Sarah Geronimo. Ms. Pia emanates the personality of Filipino millennials who are career-driven, passionate and determined. To effectively communicate the campaign to the target audience, the researcher will use both traditional and new media. The media plan was strategically scheduled based on consumers daily routine and lifestyle.